Benefits of partially hydrolyzed whey protein infant formulas - E. A. Turganova; T. N. Elkina; E. A. Surovikina (Лечащий Врач, 2025)
Introduction. The most physiological nutrition for a child from the first days of life is breast milk, which contains all the necessary nutrients, a large number of biologically active compounds and protective factors that influence growth, proper development, the formation of the immune system, programs health, protecting against a huge number of diseases. Despite the unique composition, a large number of children in the first year of life do not have the opportunity to receive breast milk in the required volume, and the pediatrician and neonatologist are faced with the task of providing nutrition, taking into account various factors: characteristics of the course of pregnancy, gestational age at the time of birth, degree of maturity, anthropometric indicators, allergy history, method of delivery, etc. The basis of the modern approach to organizing artificial and mixed feeding of children in the first year of life is the use of adapted milk formulas.Results. The article discusses mixtures with partially hydrolyzed whey protein, provides data on their safety, features of production and composition, and the possibilities of their use for children in the first year of life. Partially hydrolyzed protein is digested and metabolized faster than intact protein not only from cow's milk but also from women's milk, as evidenced by studies in animals, adults and infants. Consumption of partially hydrolyzed proteins results in their faster digestion and absorption, increasing amino acid availability. Partially hydrolyzed protein in the small intestinal phase of digestion requires fewer enzymes, the key ones being enterokinase and trypsin. Absorption of the final products of protein cleavage (diand tripeptides) from partially hydrolyzed protein occurs across the small intestine more rapidly than from whole protein. During the final breakdown of the hydrolysate to amino acids, which takes place in the cytoplasm of enterocytes with their further entry into the systemic bloodstream, oligopeptides do not compete for transport systems with free amino acids, thus ensuring a progressive and gradual process of their absorption.